Assessment of Low Back Pain in Helicopter Pilots Using Electrical Bio-Impedance Technique: A Feasibility Study - Wang, Hang; Dai, Jing; Wang, Chunchen; Gao, Zhijun; Liu, Yang; Dai, Meng; Zhao, Zhanqi; Yang, Lin; Tan, Guodong (Frontiers in Neuroscience, 2022)
Low back pain (LBP) is known to pose a serious threat to helicopter pilots. This study aimed to explore the potential of electrical bio-impedance (EBI) technique with the advantages of no radiation, non-invasiveness and low cost, which is intended to be used as a daily detection tool to assess LBP in primary aviation medical units. The LBP scales (severity) in 72 helicopter pilots were assessed using a pain questionnaire, while the bilateral impedance measurements of the lumbar muscle were carried out with a high precision EBI measurement system. Results showed that the modulus of lumbar muscle impedance increased with LBP scale whereas the phase angle decreased. For different LBP scales, significant differences were found in the modulus of lumbar muscle impedance sum on both sides (Zsum), as well as in the modulus and phase angle of lumbar muscle impedance difference between both sides (Zdiff and ϕdiff), respectively (P < 0.05). Moreover, Spearman’s correlation analysis manifested a strong correlation between Zsum and LBP scale (R = 0.692, P < 0.01), an excellent correlation between Zdiff and LBP scale (R = 0.86, P < 0.01), and a desirable correlation between ϕdiff and LBP scale (R = −0.858, P < 0.01). In addition, receiver operator characteristic analysis showed that for LBP prediction, the area under receiver operator characteristic curve of Zsum, Zdiff, and ϕdiff were 0.931, 0.992, and 0.965, respectively. These findings demonstrated that EBI could sensitively and accurately detect the state of lumbar muscle associated with LBP, which might be the potential tool for daily detection of LBP in primary aviation medical units.